Fermented sugarcane juice-derived probiotic Levilactobacillus brevis RAMULAB54 enhances lipid metabolism and glucose homeostasis through PPAR-γ activation - Kumari, V. B. Chandana; Ramu, Ramith; Huligere, Sujay S.; Patil, Shashank M.; Nayakvadi, Shivasharanappa; Bijoor, Sharath; Manjappara, Uma Venkateswaran; Ahmed, Mohammad Z.; Wong, Ling Shing (Frontiers in Microbiology, 2025)
The gut microbiota plays a significant role in metabolic disorders such as diabetes and obesity, with the peroxisome proliferator-activated receptor gamma (PPAR-γ) being a key regulator in adipogenesis and glucose metabolism. This study is a novel approach that explores the antihyperglycemic and antihyperlipidemic effects of Levilactobacillus brevis RAMULAB54 (LB13243), isolated from fermented sugarcane juice. LB13243 was cultured for SEM imaging, and its supernatant (LBR54) was analyzed. Organic acid interactions with PPAR-γ were evaluated via molecular docking, while cytotoxicity and adipocyte differentiation in 3T3-L1 cells were tested using MTT assays, Oil Red O staining, triglyceride quantification, and qRT-PCR. In vivo, male Wistar rats in hyperlipidemic and streptozotocin-induced hyperglycemic models were treated with LB13243 for 4 weeks, followed by analysis of food intake, body weight, serum glucose, lipids, and histopathology. LB13243 inhibited carbohydrate-hydrolyzing enzymes and showed an organic acid profile. In silico, hydroxycitric acid had similar binding to PPARγ as rosiglitazone (binding energy:−8.4 kcal/mol vs.−8.3 kcal/mol), with greater stability (RMSD: 1.2 Å vs. 1.7 Å). Pharmacokinetics indicated moderate GI absorption (20%) and low toxicity for hydroxycitric acid. LBR54 did not affect 3T3-L1 cell viability but reduced lipid accumulation by 13% and triglycerides by ≤ 44 mg/dL. qRT-PCR revealed upregulation of PPAR-γ and C/EBP-α, and downregulation of FAS, suggesting modulation of adipogenesis. In vivo, LB13243 reduced food intake, weight gain, and normalized organ weights in hyperlipidemic rats, while improving glucose levels and lipid profiles in hyperglycemic models. Histopathology showed improved tissue structure, indicating LB13243's potential to reduce hyperglycemia and hyperlipidemia by modulating lipid metabolism and inflammation. LB13243's modulation of PPAR-γ suggests it as a promising natural option for managing diabetes and hyperlipidemia. This study also highlights LB13243's distinctive capability to modulate PPAR-γ through its organic acids, particularly hydroxycitric acid, providing novel insights into its therapeutic potential.